2017
DOI: 10.4236/ampc.2017.74009
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Contact and the Evaporation Kinetics of a Thin Water Liquid Bridge between Two Hydrophobic Plates

Abstract: The evaporation of sessile water droplets on hydrophobic surfaces is a topic which led to numerous investigations. However, how does the liquid behave when the evaporation occurs between two of these particular substrates? The drying stage is governed by capillary phenomena which takes place in a confined space. In the field of material shaping, it is also possible that some regions of a green body exhibit hydrophobic properties. As part of a better understanding of the local mechanisms during drying, liquid b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
(19 reference statements)
1
5
0
Order By: Relevance
“…For water droplets of 5 μL volume, the receding contact angle on the glass substrate is 20°. 43 Previous studies 13,16 have also evinced the instability characteristics of liquid bridges near this point. For the minimum volume instability, the liquid bridge ruptures from the neck region to form isolated droplets on both the top and bottom substrates.…”
Section: ■ Materials and Methodsmentioning
confidence: 86%
See 2 more Smart Citations
“…For water droplets of 5 μL volume, the receding contact angle on the glass substrate is 20°. 43 Previous studies 13,16 have also evinced the instability characteristics of liquid bridges near this point. For the minimum volume instability, the liquid bridge ruptures from the neck region to form isolated droplets on both the top and bottom substrates.…”
Section: ■ Materials and Methodsmentioning
confidence: 86%
“…In general, the contact line depins near this point, as reported in previous studies. 13,19 In the case of CCR mode of evaporation on hydrophilic surfaces (θ 0 = π/6, π/3), the liquid bridges may become unstable due to either minimum volume instability or depining instability. 20 The onset of depining may be characterized by specifying the receding contact angle of water.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The involvement of hydrophobic attraction between alkyl-modified particles during their assembly into CCs needs further confirmation because research on hydrophobic forces is limited to aqueous environments, and their magnitude in other solvents is still unexplored, particularly when there is chemical heterogeneity at the nanometer scale. Studies have shown that the presence of hydrophilic groups, immobilized on alkyl-modified surfaces or coexisting with hydrophobic domains in proteins, can modulate hydrophobic forces in different ways going from completely nullifying them to doubling their strength. ,, Moreover, during the wet stage and the late stage of nano dewetting (interparticle liquid bridges), the strength of capillary forces driven by the liquid–air interfacial tension between particles depends on the hydrophobicity of the particle surface because the contact angle of the solvent at the particle surface increases with its hydrophobicity. Besides the effect on particle–particle interactions during evaporative assembly, particle surface hydrophobicity affects particle–hydrophilic substrate interactions. Only few studies have investigated similar asymmetric hydrophobic–hydrophilic surface interactions, all of which were measured in aqueous solutions. Donaldson et al.…”
Section: Resultsmentioning
confidence: 99%
“…The complex cases of the evaporation of a capillary bridge between one sphere and a surface [8] or between two spheres have been studied considering both evaporation kinetics [9] and bridge break-up [10]. Recently, the evaporation of a capillary bridge between two plates has been extensively explored in well-controlled conditions by Portuguez et al [11,12] for different wetting angles and air humidities. However, capillary forces of evaporating liquid bridges were not directly measured with their set-up.…”
Section: Introductionmentioning
confidence: 99%